Tinjauan Ornamen Cina pada Atap Masjid Tan Kok Liong, Depok, Indonesia: : Studi Perbandingan dengan Masjid Agung Xi'an, Cina - Darmayanti, Tessa Eka; Muliati, Amanda; Amadea, Annisa Rahma (Program Studi Desain Interior Unikom, 2019)
This review covers the observation of Chinese ornaments on the roof of Tan Kok Liong Mosque compared with The Great Mosque of Xiâ€™an in China. The method used in this study is descriptive method with qualitative approach. This study was conducted on Tan Kok Liong Mosque, which is located in Cibinong, Indonesia and on The Great Mosque of Xiâ€™an located in Shaanxi Province, China. The data were collected from the field observations and interviews with the designer, owner, Islamic leader, the Mosque caretakers, and the local residents who are familiar with the components and history of both Mosques. Exploratory literature also used to support and strengthen existing data. The data were analyzed by describing, presenting, and verifying by using the theories of culture and meaning (semiotics). There are five ornaments on the roof of Tan Kok Liong Mosque, there are; bao ding (å®é¡¶), dun shou (è¹²å…½), chui shou (åž‚å…½), arched roof, and ceramics that cover the roof. The result of this study shows that there is a relation between the ornaments and the Chinese culture, although not entirely the same, but still have the same essence with the ornaments on The Great Mosque of Xiâ€™an. The contribution that can be given from this research is to broaden knowledge about the use and the meaning of Chinese ornaments used on the roof of mosque buildings in two different countries.Other than that, it can be a new source of literature for future research.